2019
DOI: 10.3390/ani9100773
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas Production Recording System and Pig Fecal Inoculum Volume on Kinetics and Variation of In Vitro Fermentation using Corn Distiller’s Dried Grains with Solubles and Soybean Hulls

Abstract: Simple SummaryVarious in vitro methodologies have been developed and used to estimate the digestibility of feed ingredients, such as corn distillers dried grains with solubles (cDDGS) and soybean hulls (SBH) which contain high concentrations of dietary fiber. This study evaluated two in vitro gas production recording systems (manual vs. automated) and two initial fecal inoculum volumes (30 vs. 75 mL) on the parameters of in vitro fermentation of cDDGS and SBH. The results showed that the use of 75-mL inoculum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…Total tract DM digestibility values were calculated from pooled samples and were greater than 75% for all coproducts except US-HP49 (63.54%). These results are consistent with those reported by Huang et al (2017a , 2017b ) and Jang et al (2019) . For example, Huang et al (2017a) reported that IVDMD t of 16 corn DDGS sources ranged from 76.0% to 83.5%.…”
Section: Resultssupporting
confidence: 94%
“…Total tract DM digestibility values were calculated from pooled samples and were greater than 75% for all coproducts except US-HP49 (63.54%). These results are consistent with those reported by Huang et al (2017a , 2017b ) and Jang et al (2019) . For example, Huang et al (2017a) reported that IVDMD t of 16 corn DDGS sources ranged from 76.0% to 83.5%.…”
Section: Resultssupporting
confidence: 94%
“…The in vitro dry matter digestibility (IVDMD) analysis for each sample was performed via sequential enzymatic hydrolysis using pepsin (P7000, 421 pepsin units per mg solids, Sigma-Aldrich, St. Louis, MO, USA) and pancreatin (P1750, four times the specifications of the United States Pharmacopeia, Sigma-Aldrich) to simulate the gastric and small intestine in monogastric animals [23]. IVDMD and the in vitro digestibility of AA (IVDAA) were analyzed and calculated as reported in a previous study [10].…”
Section: Methodsmentioning
confidence: 99%
“…where: G = the gas produced at a specific time (t); A = asymptotic gas production (ml/g DM); L = the lag time before the fermentation started (h); the constants b (h −1 ) and c (h −1/2 ) determine the fractional degradation rate of the substrate µ (h −1 ), which is postulated to vary with time as proposed by Jang et al [30]:…”
Section: Experiments 1: In Vivo Digestibilitymentioning
confidence: 99%